DEVELOPMENT AND EMPOWERMENT OF MSMEs THROUGH MICRO-FINANCE IN INDONESIAN SHARIA BANK JAMBI CITY - Rafidah Rafidah; Ahmad Afwan Alwi; Lumiar Lumiar; GWI Awal Habibah (SEAN Institute, 2023)
This research is motivated by the importance of the role of Islamic banking in the development and progress of the community's economy, such as MSMEs. The objectives of this research are (1) to find out the role of Bank Syariah Indonesia in the development and empowerment of MSMEs in Jambi City after the Covid-19 pandemic. (2) To find out what are the obstacles faced by Bank Syariah Indonesia in developing and empowering MSMEs in Jambi City after the Covid-19 pandemic. 3) To find out how the solutions provided by Bank Syariah Indonesia Jambi city branch in overcoming post-pandemic constraints Covid-19 in the process of developing and empowering MSMEs in Jambi City . This research includes qualitative research with data collection methods through observation, interviews, and documentation. The data taken was in the form of primary data and secondary data. Selection of informants as data sources in research on subjects who master the problem, have data and are willing to provide information. In other words, the informant must fulfill the requirements as a source of informants. The informants in this study were Mr. Bambang Triatmojo as the Micro Relationship Manager of Bank Syariah Indonesia Jambi City and several MSMEs in the Jambi city area who were the research samples. The analytical techniques used in this qualitative research are data collection, data reduction, data presentation and drawing conclusions. The results of the study show that in the process of interviewing and observing the intended object, it was found that Bank Syariah Indonesia has played an important role for MSMEs, because many say that all roles in Bank Syariah Indonesia are like providing assistance, especially in the form of financing, consulting on business development. , business guidance through seminars or conducting comparative studies with similar businesses that have developed have been proven. The obstacles faced by the bank are the lack of outreach to the public regarding the products and services offered by the bank and the age of the company merger which is only one year so that the program that should be running is not optimal. Constraints that are often complained of by SMEs are capital, marketing and distribution problems. This can be addressed by optimizing its role through bank products and services in the form of financing, training and assistance in developing and empowering MSMEs in Jambi City. Then the community is expected to be able to take advantage of the facilities provided by Bank Syariah Indonesia as an alternative solution to overcome obstacles that arise in the process of developing and empowering their business after the Covid-19 pandemic